Land Tenure System and Security of Kumal Community in Gorkha - Gurung, Chan Bahadur (Journal of Advanced Academic Research, 2023)
This paper analyzes the land tenure system, its history, demographic and socio-economic characteristics and tenure ownership and security of Kumal community in Gorkha district of Nepal. Land is a fundamental natural resource for living, an economic asset for production, legal entity with multiple rights over it and above all, a societal factor for self-actualization. So, ownership of land has multi-faceted understanding. The objective of this paper is to analyze the existing land tenure system of Kumal community of Gorkha by reviewing the history of the tenure system and current tenure system, and carrying out HH survey to improve the tenure ownership and security. However, the tenure rights of socially and economically disadvantaged community like Kumals have not been properly addressed and those people are at high risk of eviction from the place they are living. The study recommends that land tenure insecurity arising from political, legislative and organizational behavior should be managed by appropriate interventions and policy reforms. As most of the analyses of land tenure security in Nepal have been performed in a descriptive way, this study explicitly investigates the issue through household survey. As Nepal is in the process of implementing federalization, assessment of land tenure security shall be one of the instruments for developing new land related policies and assessing the effect of new policies afterward.